A Data Owner Controlled Model for Co tenant Covert Channel Protection (International Journal of Engineering and Computer Science, 2018)
The emerging technology cloud Computing has became as a popular choice for small and medium enterprises for their infrastructural needs. It has many services providing support like computing, storing etc. Virtualization is the key technology to provide features like scalability and elasticity using multi tenancy. In multi tenant cloud architecture malicious co tenants use covert channels like RAM, bus and other shared devices to hijack the sensitive data. Literature is available for identifying and preventing these kinds of attacks in matured cloud providers. Immature or lazy cloud service providers will suffer from these kinds of problems profoundly. Our novel model tries to suggest measures in protection of covert channel protection. It uses a simple technique of split and sharing data to store multiple regions in multiple places. We have taken factor called as missing data which is inaccessible data in the case of compromised co tenant covert channel attack. Experiments were done in the Amazon S3 cloud with different accounts in different regions and multiple buckets for storing split data and results were analyzed. We come across with best number of splits to maximize missing data factor with less impact over the time cost for upload and download operations from our result analysis satisfactorily.